Prenatal exposure to organochlorine pesticides and infant growth: A longitudinal study - Chenhui Yang; Jing Fang; Xiaojie Sun; Wenxin Zhang; Juxiao Li; Xiaomei Chen; Ling Yu; Wei Xia; Shunqing Xu; Zongwei Cai; Yuanyuan Li (Environment International, 2021)
Background: The association between exposure to organochlorine pesticides (OCPs) and infant growth has been reported contradictorily in previous studies. Few studies have investigated the effects of prenatal exposure to OCPs on infant growth assessed longitudinally at multiple time points. Objectives: The purpose of the study was to examine the associations between prenatal exposure to OCPs and infant growth at birth, 6, 12 and 24 months of age, and further to explore the potential sex-specific effects. Methods: The study population included 1039 mother-infant pairs who participated in a birth cohort study in Wuhan, China. The weight, length and body mass index (BMI) z-score of infants were measured and calculated at birth, 6, 12 and 24 months of age. The overweight status was defined as BMI z-score ≥ 85th percentile according to the standard of World Health Organization. The concentrations of OCPs were measured in cord serum, including hexachlorocyclohexanes (HCHs, consisted of α-HCH, β-HCH, and γ-HCH), p,p′-dichlorodiphenyltrichloroethane (p,p′-DDT) and its metabolites: p,p′-dichlorodiphenyldichloroethane (p,p′-DDD), and p,p′-dichlorodiphenyldichloroethylene (p,p′-DDE). Generalized linear models were applied to estimate the associations of cord OCPs with infant growth parameters. A group-based semiparametric mixture model was used to estimate growth patterns of infants. Linear-mixed growth curve models were used to examine relationships between predicted growth trajectories and prenatal exposure to OCPs. Weighted quantile sum regression (WQSR) analyses were used to estimate the mixture effects of OCPs on infant growth. Results: Higher cord serum β-HCH concentrations were associated with higher BMI z-score at 12 [β = 0.07, 95%CI: 0.01, 0.13] and 24 months of age [β = 0.08, 95% CI: 0.02, 0.14]. Similar patterns were observed for relationships of γ-HCH [β = 0.04, 95%CI: 0.01, 0.07] and p,p′-DDT [β = 0.03, 95% CI: 0.00, 0.06] with BMI z-score at 6 and 12 months of age, respectively. However, higher cord serum p,p′-DDE concentrations were associated with a reduction of BMI z-score at 6 months of age [β = −0.07, 95% CI: −0.12, −0.01]. Cord serum β-HCH was also positively associated with the risk of overweight at 12 months of age [RR = 1.16, 95% CI (1.02, 1.33), for the medium vs the lowest tertile]. Among girls, the effects of β-HCH on BMI z-score and overweight status were stronger than boys at 12 and 24 months of age. No statistically significant relationships of other OCPs with infant growth were observed. Conclusions: Prenatal exposure to β-HCH was associated with increased BMI z-score and higher risk of overweight status in infants especially at 12 and 24 months of age, which seemed to be stronger in girls.